HPLC profiling of Mimosa pudica polyphenols and their non-invasive biophysical investigations for anti-dermatoheliotic and skin reinstating potential - Walsh, John (My University, 2019)
Plant-derived polyphenols are known to have promising biological activities including antioxidant and anti-tyrosinase and may be a potential candidate for anti-dermatoheliotic remedy. The present study was performedto investigate the polyphenolic contents of Mimosa pudica (MP) seed extract and its anti-dermatoheliotic potential using non-invasive biophysical techniques after developing a stable topical emulgel formulation. Moreover, itsin-vitrocytotoxicity was also evaluated using normal Human keratinocytes (HaCat cells) to rule outany cellular incompatibility. The results revealed that MP seed extract, constituted with a number of polyphenolic compounds, has very good antioxidant and anti-tyrosinase potential. There were significant positive effects (p≤0.05) invoked by its topical emulgel formulation on various dermatoheliotic associated skin parameters like erythema, melanin, elasticity, hydration, and sebum as compared to placebo. In the meantime, it was also found to be biocompatible and did not show any effect on HaCat cell viability and structure. In conclusion,the topical emulgel preparation loaded with MP seed extract could be a great strategy to deal with dematoheliosis.
PUBLISHED
Keywords: Dermatoheliosis; Mimosa pudica; Polyphenols; Biophysical techniques; Emulgel; Skin parameters; Ageing